The Folk Epic and Theatrical Art of Central Asia - Tadjibaeva, Oltinoy Kasymovna (International Journal of Membrane Science and Technology, 2023)
This article discusses the role and importance of folk art heritage in the development of national theater art in Central Asia. To date, the theatrical art of the region has great experience and the opportunity to compare its culture with others. The epic tradition is one of the mainstays, one of the heights from which one can look at the experience and trends of world theatrical art.